PROFESSIONAL TRAINING OF THE STATE BORDER GUARD OFFICIALS OF THE REPUBLIC OF LATVIA: ESSENTIALS, CHALLENGES AND POSSIBLE SOLUTIONS - Zālītis, Ivars; Soboļeva, Diāna; Madžule, Inta (Border Security and Management, 2016)
Topicality of the Paper is determined by the dynamic and considerable changes that influence the fulfilment of the State Border Guard professional activities which in turn impose additional requirements to the professional training of border guards. The quality of the State Border Guard work reflects in its implemented functions that also results from the proficiency and professionalism of the personnel. The aim of this Paper is to analyse the current system of border guards’ professional training, regulatory aspects as well as gathered statistical data regarding the issues of presented topics. Authors of the Paper bring forward several suggestions that in future could satisfy the central demands in the field of border guards` professional education and could be successfully implemented in the Basic concepts of the State Border Guard`s personnel training.